Mechanisms for Clearing Private Real Estate Ownership Between Legislation and Judiciary - LOUSIF , Najat; MERMOUN, Moussa (Journal of Human Sciences, 2025)
The legislator aimed to address colonial-era issues by establishing an integrated real estate system to ensure stability in transactions. This led to adopting a property-based registration system, replacing the flawed personal registration method. Comprehensive land surveys were initiated to accurately identify property ownership, resulting in detailed listing and issuance of property registers.Due to slow land surveying, alternative mechanisms were introduced to expedite property deeds, such as the “Act of Fame,” which was abolished in 2007 due to its complications and impact on public and waqf properties. It was replaced by real estate investigations, and the Land Orientation Law introduced the certificate of possession.These mechanisms share common conditions: non-application in surveyed areas and protection of public, waqf, and tribal lands. However, they remain insufficient, highlighting the need for more effective tools to support land surveys and property cleansing. The judiciary is also urged to unify its stance and align with the legislator’s objectives.